Study of CPM device used for rehabilitation and effective pain management following knee alloplasty - Trochimczuk, Roman; Kuźmierowski, Tomasz; Anchimiuk, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
This paper defines the design assumptions for the construction of an original demonstration of a CPM device, based on which a solid virtual model will be created in a CAD software environment. The overall dimensions and other input parameters for the design were determined for the entire patient population according to an anatomical atlas of human measures.
Keywords: CPM device; rehabilitation robot; effective pain management; knee alloplasty; FEM analysis